Nanosecond double-pulse fiber laser with arbitrary sub-pulse combined based on a spectral beam combining system. (1st May 2017) - Hu, Man; Zheng, Ye; Yang, Yifeng; Chen, Xiaolong; Liu, Kai; Zhao, Chun; Wang, Jianhua; Qi, Yunfeng; He, Bing; Zhou, Jun
Abstract: In order to improve the processing efficiency and quality of nanosecond pulse laser drilling, a new double-pulse technique is put forward. Two single pulse lasers with different pulse duration or different repetition rate are spectrally combined by a home-made polarization-independent multilayer dielectric reflective diffraction grating. The pulse energy of single lasers and the inter-pulse separation can both be set at one's option. Then, double-pulse lasers represent two closely conjoint pulses with tunable pulse duration and tunable repetition rate and tunable pulse energy and tunable inter-pulse separation are obtained. Highlights: A spectral beam combining system based on a MLD diffraction grating is established. Three typical double-pulse lasers with arbitrary sub-pulse shapes are obtained. The inter-pulse separation of each double-pulse laser can be set at random. Several-pulse laser with more sub-pulses can be realized in this system.